Bi3+ Induced Crystal Growth of a Symbiotic Heterojunction Enables Long‐Lifespan Zn‐Ion Batteries. Issue 9 (2nd May 2022) - Gou, Lei; Wang, Wenyan; Wang, Wenqi; Zhao, Shaopan; Han, Xiao; Fan, Xiaoyong; Li, Donglin
Abstract: The MnO2 /Mn2 O3 symbiotic heterojunction is considered to be a promising cathode material for aqueous zinc‐ion batteries (ZIBs) owing to the built‐in electric field generated from the heterojunction interface that can accelerate ion transporting. However, the structure collapse caused by the Mn 3+ dissolution, leading to a sharp capacity decline, is still one of the major issues. In this work, a Bi‐doped MnO2 /Mn2 O3 symbiotic heterojunction with a uniform nanorod structure was formed due to the Bi‐induced crystal growth mechanism. In addition, Bi 3+ doped into the lattice effectively inhibited the dissolution of Mn 3+ and greatly enhanced charge transfer and reaction kinetics. Therefore, an impressive long‐term cycling performance over 6000 cycles at a current density of 2 A g −1 was obtained. Such a Bi 3+ induced symbiotic heterojunction crystal growth strategy may open new opportunities toward high‐performance aqueous ZIBs. Abstract : Aqueous zinc‐ion batteries : Bi induces the formation of a symbiotic MnO2 /Mn2 O3 heterojunction and effectively inhibits the structure collapse caused by dissolution of Mn 3+ . Thus, using Bi−MnO2 /Mn2 O3 as a cathode material leads to fast ion‐transfer kinetics and a long life over 6000 cycles for aqueous zinc‐ion batteries.